Role of Downregulation and Phosphorylation of Cofilin in Polarized Growth, MpkA Activation and Stress Response of Aspergillus fumigatus - Jia, Xiaodong; Zhang, Xi; Hu, Yingsong; Hu, Mandong; Han, Xuelin; Sun, Yansong; Han, Li (Frontiers in Microbiology, 2018)
Aspergillus fumigatus causes most of aspergillosis in clinic and comprehensive function analysis of its key protein would promote anti-aspergillosis. In a previous study, we speculated actin depolymerizing factor cofilin might be essential for A. fumigatus viability and found its overexpression upregulated oxidative response and cell wall polysaccharide synthesis of this pathogen. Here, we constructed a conditional cofilin mutant to determine the essential role of cofilin. And the role of cofilin downregulation and phosphorylation in A. fumigatus was further analyzed. Cofilin was required for the polarized growth and heat sensitivity of A. fumigatus. Downregulation of cofilin caused hyphal cytoplasmic leakage, increased the sensitivity of A. fumigatus to sodium dodecyl sulfonate but not to calcofluor white and Congo Red and farnesol, and enhanced the basal phosphorylation level of MpkA, suggesting that cofilin affected the cell wall integrity signaling. Downregulation of cofilin also increased the sensitivity of A. fumigatus to alkaline pH and H2O2. Repressing cofilin expression in A. fumigatus lead to attenuated virulence, which manifested as lower adherence and internalization rates, weaker host inflammatory response and shorter survival rate in a Galleria mellonella model. Expression of non-phosphorylated cofilin with a mutation of S5A had little impacts on A. fumigatus, whereas expression of a mimic-phosphorylated cofilin with a mutation of S5E resulted in inhibited growth, increased phospho-MpkA level, and decreased pathogenicity. In conclusion, cofilin is crucial to modulating the polarized growth, stress response, cell wall integrity and virulence of A. fumigatus.